Effects of fractional order integration on ASDM signals - Kavuran, Gurkan; Yeroğlu, Celaleddin; Ateş, Abdullah; Alagoz, Baris Baykant (Springer Berlin Heidelberg, 2017)
Pulse density modulation (PDM) can find applications in consumer electronics, power and switch control systems. PDM signals can be generated by asynchronous sigma delta modulator (ASDM) structures and improvement of ASDM performance provides significant contribution for practical applications. This study numerically investigates effects of fractional order integration (FOI) on the PDM signal, produced by ASDM. We implemented fractional order integratorin ASDM structure and present numerical analysis to discuss effects of fractional order integrator on PDM signals, obtained for bipolar digital signal transmission application. Theoretical analysis indicates that FOI provides finer pulse trains and thus improves representation of original signal. In simulations, we tested FOI for various fractional-order values. Signal to noise ratio and signal to noise and distortion ratio (SINAD) levels of demodulated signals are reported for sinusoidal and audio test signals. Simulation results demonstrate that FOI can improve SNR and SINAD performance of ASDMs. © 2016, Springer-Verlag Berlin Heidelberg.
Keywords: Asynchronous sigma delta modulator; Fractional order integration; PDM; SNR